High expression of GLI1 is associated with better survival in advanced SCLC - Kozirovskis, V.; Zandberga, E.; Magone, M.; Purkalne, G.; Linē, A.; Vikmanis, U. (PH Akademperiodyka, 2023)
Summary. Aim: Aberrant Sonic hedgehog (Shh) pathway signaling has been described in small cell lung cancer (SCLC), as well discrepancies, when analyzing expression of pathway components in SCLC cell lines vs tumor biopsies. Shh key component GLI1 was evaluated in advanced SCLC and data correlated with patient survival. Materials and Methods: GLI1 expression was analyzed by quantitative real-time polymerase chain reaction in pre-treatment fresh frozen tumor biopsies of 12 advanced SCLC patients and mRNA level of GLI1 was compared in short-term vs long-term survivor’s samples (stratified by median survival, independent samples t-test). Results: Expression of GLI1 mRNA was significantly higher in long-term (> 9.6 months, n = 6) survivor’s biopsies than in short-term (≤ 9.6 months, n = 6) survivors (p = 0.0196, 95% CI: 0.000016 to 0.000147, two-tailed independent samples t-test). Conclusion: High GLI1 mRNA expression in SCLC was found to be positive prognostic marker associated with longer survival. Further research is needed for validation of these results due to the small number of patients in the study.